Comparative reproductive success of communally breeding burying beetles as assessed by PCR with randomly amplified polymorphic DNA. - Scott, M P (1993)
To understand the evolution of alternative reproductive strategies such as communal breeding, it is important to recognize the options open to individuals and to evaluate their consequences. The relative reproductive success of individuals taking each option is one of the most important of these consequences. Burying beetles, Nicrophorus, are an excellent model system for the investigation of reproductive cooperation because they can breed in pairs or communally and provide extensive parental care. In this study, we examine the relationship of the duration of care and the reproductive success of each potentially communally breeding adult. Ten experimental broods reared on mouse carcasses were buried by two males and two females. Using PCR with single short primers that randomly amplify polymorphic DNA, we determined the maternity and paternity of 98.2% and 99.5% of the offspring (n = 217), respectively. In 70% of the broods, both females produced larvae, and in 70%, both males inseminated one or both females. The male and female providing longer care, usually the larger of each sex, were the mother and father of most larvae (50-100%).